Recognizing the elbow prosthesis on conventional radiographs - Oflazoglu, Kamilcan (Strategies Trauma Limb Reconstr, 2016)
The objective of this study was to make an overview that can be useful in determining which type and brand of prosthesis a patient has when visiting the emergency department or outpatient clinic with a periprosthetic fracture, dislocation, or implant failure. The commonly used prostheses in Europe are opted for this list. The radiographs used for this list are obtained either from the company or from our own patients. This list contains the Coonrad/Morrey total elbow prosthesis, the Nexel total elbow prosthesis, the GSB III Elbow Prosthesis, the iBP Total Elbow System, the Discovery Elbow System, the NESimplavit Elbow System, the Latitude Elbow prosthesis, the Solar Elbow, and the Souter–Strathclyde total elbow. The characteristics of each prosthesis are described.